Analisis Penggunaan Multimedia Pembelajaran Interaktif terhadap Motivasi Belajar Peserta Didik pada Mata Pelajaran Matematika - Saepuloh Saepuloh; Khomsatun Ni'mah (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
The purpose of this study was to determine and identify the extent how far the use of computer-based interactive multimedia made by the Lectora application on the motivation of students and their responses. The author uses qualitative research method with a descriptive approach. The research was held at MA Assa'adah Jamanis Tasikmalaya. The research subjects were students and mathematics teachers 10th grade. The selection was made purposively. Because of the Covid 19 pandemic condition, the number of students is limited to 50% of the computer laboratory capacity, which is 16 people. The technique of collection data are semi-structured interviews, observation of active participation in data collection, and documentation. The instruments used in this study are (1) interview instruments, (2) observation instruments, (3) document instruments. Data were analyzed using the Analysis Interactive model with several stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that the use of interactive multimedia learning media, students were  motivated and active. They feel happy and challenged. They also don't feel bored when they are at the computer. This learning media presents material complete and attractive material. This interactive learning media is easy to use, contains mathematical concepts, material can be repeated, both written and video material. This media can create a more focused learning condition. The media is relevant to the material being studied. However, it is important to note, that although technology can be learning resource, it still cannot replace the teacher's position.